2019
DOI: 10.1016/j.arthro.2019.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Is Arthroscopic Bankart Repair Using Suture Anchors on the Glenoid Appropriate Treatment for Traumatic Anterior Shoulder Instability?

Abstract: Fracture of the anterior glenoid rim along the sites of suture anchor insertion is not rare after arthroscopic Bankart repair for traumatic anterior shoulder instability. In addition to the influence of the number, type, and size of the suture anchors, placing multiple anchors in a linear arrangement might impose excessive stress on the surrounding bone, leading to critical loss of osseous integrity and glenoid fracture. Although highly active young male collision or contact athletes are most at risk, such fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In 2018, A. Studies have shown that the number, type and size of the suture anchors and the linear arrangement of multiple anchors have important effects on postoperative glenoid fracture and recurrent shoulder instability 15 . For larger glenoid fractures, it has been reported that the use of at least three anchors during arthroscopic surgery is recommended to reduce the incidence of postoperative unstable recurrence 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, A. Studies have shown that the number, type and size of the suture anchors and the linear arrangement of multiple anchors have important effects on postoperative glenoid fracture and recurrent shoulder instability 15 . For larger glenoid fractures, it has been reported that the use of at least three anchors during arthroscopic surgery is recommended to reduce the incidence of postoperative unstable recurrence 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The Arthroscopy Association of North America Proficiency-Based Training program, developed through the Copernicus project, emphasizes the technical steps considered essential for arthroscopic success. 2,3 They include an anterosuperior viewing portal, an anteroinferior working portal abutting the superior subscapularis border, capsulolabral mobilization allowing clear viewing of the subscapularis muscle, proper insertion of 3 anchors, 4 cannulated suture hook or retriever placement inferior to the anchor site and at or peripheral to the capsulolabral junction, and proper arthroscopic knot tying including at least 3 half hitches to reinforce the initial knot.…”
Section: See Related Article On Page 862mentioning
confidence: 99%
“… 11 Naturally, the latter approach is advantageous in terms of cost and length of surgery. Moreover, a large number of anchors inserted into the anterior glenoid rim can cause excessive non-physiological stress and subsequentially bony avulsion of the anterior glenoid, termed “postage-stamp fracture.” 12 Additional studies are required to compare the two surgical methods. There are currently not enough controlled studies to resolve this issue.…”
Section: The Risk Factorsmentioning
confidence: 99%